A mode-adjustable phase-field model for brittle fracture by regulating distortional crack driving energy. (December 2022) - Hao, Liulei; Yu, Hongjun; Zhu, Shuai; Shen, Zhen; Shen, Rilin; Huang, Kai; Guo, Licheng
Graphical abstract: Highlights: A mode-adjustable phase-field model is proposed by introducing a weight parameter. The weight paramter can regulate the distortional crack driving energy. An experiment-simulation combination method is provided to determine the weight parameter. The proposed model is helpful for capture and understand the fracture features of diverse materials. Abstract: A mode-adjustable phase-field model is proposed by introducing a weight parameter to regulate the relative contribution of the volumetric and distortional crack driving energy. Altering the weight parameter results in the change of cracking mode. The weight parameter can be considered as a material parameter and determined through the comparison of experimental and simulated results. The proposed phase-field model is employed to simulate the fracture experiments for polymethylmethacrylate and Al 7075-T651 aluminum. Applying the experimentally determined parameter, the mode-adjustable phase-field model provides better simulations than the classical phase-field model for both materials. Afterwards, a shear test of a single edge notched plate is simulated and the results show that for the volumetric-deviatoric split method, as the weight parameter increases, the failure pattern during crack propagation exhibits a transition from the mode-I dominant failure to the mode-II dominant failure gradually. On the contrary, a mode-I dominant cracking always occurs with the initial crack deflection angle of about 70.5°, regardless of the value of weight parameter for the spectral decomposition split method. To summarize, the proposed mode-adjustable phase-field model can reflect the difference of crack driving mechanism, which is helpful for capturing and understanding the fracture characteristics of diverse materials.